Science Literacy-Based Student Worksheets to Improve Critical Thinking Skills on Acid-Base Materials - Eka Haslinda Fatmawati; Rusmini Rusmini (Universitas Pendidikan Mandalika, 2023)
The goal of this study was to find out the eligibility of science literacy-based student worksheets to improve learners critical thinking skills on acid-base materials. The eligibility of the developed science literacy-based student worksheets viewed from validity, practicality, and effectiveness. This type of study uses Research and Development (R&D) with a 4D research model. This study model consists of the define, design, and limited to develop stages. The validity of science literacy-based student worksheets based on content criteria obtained a percentage of 37.50% (valid) with mode 3 and 62.50% (very valid) with mode 4. On the construction criteria, obtain a percentage of 15.15% (valid) in mode 3 and 84.85% (very valid) in mode 4. The practicality of the student worksheet was viewed from the responses and observations of learner activities, which earned a percentage of 97.10% and 90% with very practical criteria. The effectiveness of the student worksheet received highly effective criteria viewed from the N-gain score of science literacy of 0.75 (high), and critical thinking skills obtained a N-gain score of 0.71 (high). This is corroborated by the Wilcoxon statistical test of science literacy and critical thinking skills, which revealed a disparity between learners' capability for science literacy and critical thinking skills prior to and following the use of science literacy-based student worksheets, with a sig. (2-tailed) of 0.000. The Spearman correlation test resulted in a correlation coefficient of 0.754, indicating a significant association between science literacy and critical thinking skills, with a classical completeness of 89%. So, based on this research, science literacy-based student worksheets are declared eligible to improve learners thinking skills.